CAD feature recognition as a means to prevent ergonomics issues during manual assembly tasks. Issue 5 (3rd September 2018) - Marconi, Marco; Germani, Michele; Favi, Claudio; Raffaeli, Roberto
ABSTRACT: Feature-based modeling and feature recognition algorithm are state of the art technologies, mainly used to favor the integration and exchange of data between design and manufacturing phases. This paper aims to investigate the possibility to extend the use of the feature recognition as a means for the prevention of ergonomics issues during the manual assembly phase, such as Work-related Musculo-Skeletal Disorders (WMSDs). Starting from the features analysis of a 3D product model, the proposed five steps method allows preventively identifying potential ergonomics issues. The main novelty of this study is related to the correlation between design tools, product virtual representations (e.g. 3D models), assembly and ergonomics aspects. Results obtained with two case studies, a cooker hood and a tool-holder carousel, confirm the usefulness of the proposed method in helping designers to prevent potential ergonomics issues for operators involved in the assembly phase. GRAPHICAL ABSTRACT: